CALORIC CONTENT OF METAPENAEUS DOBSONI - Vijayaraghavan, Sumitra; Vijayakumaran, M (Indian Journal of Fisheries, 2011)
The caloric content of the entire animal is an important variable to be determined in energy flow studies, for its knowledge makes it possible to express dry weight in terms of energy units. Hence, much effort has been made earlier to measure the caloric content of the tissues of many organisms (Slobodkin and Richman 1961, Paine and Vadas 1969, Cummins and Wuycheck 1971, Snow 1972, Qasim and Jacob 1972, Piatt and Irwin 1973 and Qasim et al 1973). Biochemical constituents of animals are known to vary with seasons, size of the animals, stages of maturity and the availability of food. These in turn aflect the caloric content of the animal. In the present study, an attempt has been made to estimate the caloric content of different size groups of male and female prawns, Metapenaeus dobsoni using three available methods. This was done to evaluate the extent to which the caloric values of this species vary with size and sex.